PENENTUAN KADAR ALKOHOL PADA TUAK AREN YANG DIPERJUALBELIKAN DI NAGORI DOLOK KECAMATAN SILAU KAHEAN KABUPATEN SIMALUNGUN SUMATERA UTARA - Maniur Arianto Siahaan; Erdiana Gultom (JURNAL KIMIA SAINTEK DAN PENDIDIKAN, 2019)
Alcohol is an organic compound that can affect the central nerves and layers of the human body to some extent. Fermented sugar palm is a type of alcoholic beverage that is also made from various types of sugar palm. The purpose of this study was conducted to determine the level of alcohol contained in sugar palm and to determine the type of alcoholic drink from sugar palm. The method used in this study is destrictive using the distillation method. The test results obtained alcoholic sugar from sugar of 4.93-8.47% alcoholic drinks included, both in samples A and B. Sample A contains 1-5% alcohol and Sample B contains 5-20% alcohol. The results obtained from research on the determination of alcohol levels in sugar palm have fulfilled the requirements of Permenkes.